Tree species composition of UiTM Jengka forest reserves between line 8 and line 9 / Mohamad Nor Afzam Md Arsad and Syazwan Firdaus Manshor - Md Arsad, Mohamad Nor Afzam; Manshor, Syazwan Firdaus (2009)
One of experiment was did to study about tree species composition between line 8 and 9 in UiTM Jengka Forest Reserve. This forest was categorized as a "Red Meranti-Keruing Forest". Area of study was cover 20m x 100m and the area is flat. From our study, there are a various types of species that live as a random especially Kedondong (Santiria spp.). Among the Kedondong species are Kedondong Kerantai, Kedondong Kerantai Licin, and Kedondong Bulan. Kedondong species is a Euphorbiaceae family. Other species that was in Euphorbiaceae family are Croton spp, Blumeodendron spp, Sapium baccatum, Macarangga spp, Aporosa and Pimelodendron griffithianum. That have 23 family and 35 species was founded. Average diameter at breast high (DBH) of trees that we study is a 9.4cm for each areas.